The Indonesian National Single Window (INSW) System On Import Goods Handling Of Mt. Asia Aspara By Pt. Samudra Shipping Agency Dumai - Sinar Siregar; Syarifur Ridho; Dina Rispianti (Jurnal Publikasi Ilmu Manajemen, 2024)
This study aims to analyze the flow of use of the Indonesia National Single Window (INSW) for handling imported goods at PT. Samudra Shipping Agency, and analyze the effectiveness of the implementation of the INSW system at PT. Samudra Shipping Agency. This study explains the differences experienced before and after the INSW system is implemented. The research method used is qualitative descriptive research. The results of the study indicate that the Indonesia National Single Window (INSW) system is effective in helping the process of handling imported goods at PT. Samudra Shipping Agency. This is because the Indonesia National Single Window (INSW) system has a significant influence and overall its implementation at PT. Samudra Shipping Agency is in accordance with the objectives of the INSW system, namely to increase the speed of service and effectiveness of supervision, as well as the performance of all activities related to the flow of export and import goods and minimize the time and costs required in all handling activities for the flow of export and import goods, especially those related to the licensing process for the release of goods. This impact is felt by the acceleration of time and reduction of costs in the process of handling imported goods at PT. Samudra Shipping Agency which is illustrated through the statements of the parties who have been interviewed.